Effectiveness of Local Point Acupuncture and Ear Acupuncture in Patients with Knee Pain at Sehat Bugar Akupunktur, Bandung - Siti Johariyah Johariyah; Purwanto; Sri Widyastari (HAKTI : Indonesian Acupuncture Therapists Association, 2026)
Knee pain is a common complaint in adults and the elderly. Treatment for osteoarthritis patients includes non-pharmacological, pharmacological, and surgical therapies. Nonsteroidal anti-inflammatory drugs (NSAIDs) are used, but NSAIDs cause side effects on the gastrointestinal and cardiovascular systems, limiting their use among patients with OAC. One such non-pharmacological therapy is acupuncture and ear acupuncture. To determine the difference in effectiveness between local acupuncture and ear acupuncture on the WOMAC (Western Ontario and McMaster Universities Arthritis Index) score of knee pain patients at Sehat Bugar Akupunktur, Bandung. A quasi-experimental study design with a two-group pre- and post-test design was used. A sample of 38 individuals experiencing knee pain who met the inclusion and exclusion criteria was divided into two treatment groups of 19 individuals each. The first group received local acupuncture, and the second group received ear acupuncture. The intervention was carried out 10 times twice a week, for five weeks. Pain was assessed using the WOMAC questionnaire. Data were analyzed using paired sample t-tests and independent sample t-tests at a significance level of 0.05. Both local acupuncture and ear acupuncture have been shown to reduce WOMAC scores, but there was no significant difference between the two.